Life at Home and on the Roam: Genomic Adaptions Reflect the Dual Lifestyle of an Intracellular, Facultative Symbiont - Ilia Burgsdorf (American Society for Microbiology, 2019)
ABSTRACT “Candidatus Synechococcus feldmannii” is a facultative intracellular symbiont of the Atlanto-Mediterranean sponge Petrosia ficiformis. Genomic information of sponge-associated cyanobacteria derives thus far from the obligate and extracellular symbiont “Candidatus Synechococcus spongiarum.” Here we utilized a differential methylation-based approach for bacterial DNA enrichment combined with metagenomics to obtain the first draft genomes of “Ca. Synechococcus feldmannii.” By comparative genomics, we revealed that some genomic features (e.g., iron transport mediated by siderophores, eukaryotic-like proteins, and defense mechanisms, like CRISPR-Cas [clustered regularly interspaced short palindromic repeats-associated proteins]) are unique to both symbiont types and absent or rare in the genomes of taxonomically related free-living cyanobacteria. These genomic features likely enable life under the conditions found inside the sponge host. Interestingly, there are many genomic features that are shared by “Ca. Synechococcus feldmannii” and free-living cyanobacteria, while they are absent in the obligate symbiont “Ca. Synechococcus spongiarum.” These include genes related to cell surface structures, genetic regulation, and responses to environmental stress, as well as the composition of photosynthetic genes and DNA metabolism. We speculate that the presence of these genes confers on “Ca. Synechococcus feldmannii” its facultative nature (i.e., the ability to respond to a less stable environment when free-living). Our comparative analysis revealed that distinct genomic features depend on the nature of the symbiotic interaction: facultative and intracellular versus obligate and extracellular. IMPORTANCE Given the evolutionary position of sponges as one of the earliest phyla to depart from the metazoan stem lineage, studies on their distinct and exceptionally diverse microbial communities should yield a better understanding of the origin of animal-bacterium interactions. While genomes of several extracellular sponge symbionts have been published, the intracellular symbionts have, so far, been elusive. Here we compare the genomes of two unicellular cyanobacterial sponge symbionts that share an ancestor but followed different evolutionary paths—one became intracellular and the other extracellular. Counterintuitively, the intracellular cyanobacteria are facultative, while the extracellular ones are obligate. By sequencing the genomes of the intracellular cyanobacteria and comparing them to the genomes of the extracellular symbionts and related free-living cyanobacteria, we show how three different cyanobacterial lifestyles are reflected by adaptive genomic features.